IMPROVING THE CONTENT OF INTEGRATIVE LESSONS IN TEACHING PHYSICS IN ACADEMIC LYCEUMS (Scientific journal of the Fergana State University, 2023)
The article presents the methods of organizing integrative lessons in the teaching of physics. Organization of physics lessons in this form forms knowledge, skills, competence and creativity in students. The purpose of the research is to describe the results of the research on the content and methodology of organizing integrative classes in the teaching of physics in academic lyceums. Observation, comparison, questionnaires, analysis and mathematical statistics methods were used in conducting the research. In the study, comments and practical proposals were developed on the content of physics and the methodology of organizing and conducting integrative classes in academic lyceums. Applying the principle of activity to improve the effectiveness of physical education classes in research, as a result of an integrative and systematic approach in modern physics, students will have comprehensive knowledge, and students will develop their independent research and creative abilities. special importance is attached to the principle of independence. It is possible to introduce a certain set of conditions and procedures of a didactic-methodological nature to the inter-disciplinary integration of topics related to physics departments using integrative methods. Such conditions and procedures should be considered as a condition for ensuring the integration of physical knowledge.